Diameter optimization of district heating and cooling piping network based on hourly load - Zeng, Jing; Han, Jie; Zhang, Guoqiang (Applied thermal engineering, 2016)
•A mathematical model of annual equivalent cost of DHC piping network is established based on hourly load.•An improved genetic algorithm is proposed bases on genetic operators: crossover, mutation and recombination.•Optimal diameters of the DHC piping network are obtained.•The change of electricity price has little effect on the optimal pipe diameter combination. In order to reduce the annual equivalent cost of a district heating and cooling (DHC) piping network, the optimal diameter combination of DHC piping network need to be determined. In this study, a mathematical model of annual equivalent cost of the DHC piping network was established based on the hourly load of substations. The model was solved by integer-coded genetic algorithm based on improved genetic operators: crossover, mutation and recombination. Two DHC piping networks, one with conventional central circulating pump (CCCP) system, and the other with distributed variable speed pumps (DVSP) system, were investigated in relation to the changes of electricity price. It was found that electricity price had little effect on the optimal pipe diameter combination and the annual equivalent cost of the DHC using a DVSP system is 20.8–27.7% lower than that of a CCCP system.